IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM MANAGEMENT AT SD IT ASH-SHIDDIQIYYAH BERJAN PURWOREJO - Musolin, Muhlil (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2024)
This study aimed to determine the implementation of independent learning curriculum management at SD IT Ash-Shiddiqiyyah Berjan Purworejo. The type of research used is qualitative research, and the method used in data collection is by conducting in-depth observations, in-depth interviews and documentation, then data analysis techniques through the data reduction stage, data presentation and conclusion. The results of the study show that the implementation of the independent learning curriculum at SD IT Ash-Shiddiqiyyah Berjan Purworejo started in the 2022/2023 academic year gradually, namely for grades one and four. The implementation of independent learning curriculum management at SD IT Ash-Shiddiqiyyah Berjan Purworejo follows curriculum management functions, namely planning, organizing, implementing and evaluating. Planning is carried out through the stages of analyzing the condition of the school and needs analysis and is determined through meetings. The organizing process is done by determining the curriculum design and developing a master plan. Implementation of the curriculum is divided into several activities, namely the activities of the principal, educators (teachers), student activities, learning process activities and non-academic development activities, and learning media maintenance activities. The evaluation uses the CIPP model (Context, Input, Process, Product).